Storm of visions - Dodd, Christina (New York : Signet Book, 2009)
"Jacqueline Vargha has always run from her gift. Now Caleb D'Angelo forces his way into her life, demands his place as her lover, and insists she take her place as one of the Chosen. She flees, he pursues, but she can no longer deny her visions, or the dangerous man who is her downfall -- and her destiny" -- from author's web site.
Includes sneak peek at title "Storm of shadows", (p. [379] -388).
Keywords: Twins -- Fiction; Good and evil -- Fiction; Occult fiction; Love stories